Tumor lysis syndrome and collateral immune activation in dual checkpoint blockade. Issue 2 (23rd November 2020) - Konishi, Risa; Ishitsuka, Yosuke; Imai, Hidemi; Inoue, Sae; Nakamura, Yoshiyuki; Okiyama, Naoko; Oshika, Tetsuro; Hiraoka, Takahiro; Fujisawa, Yasuhiro
Abstract : We describe a 69‐year‐old male Japanese with metastatic uveal melanoma who developed tumor lysis syndrome (TLS) and a series of immune‐related adverse events after repeated doses of nivolumab plus ipilimumab. TLS in advanced melanoma patients is relatively uncommon, and our report may delineate "the triple‐edged sword" aspect of dual checkpoint blockade in high‐risk cases.